Four-electrode electrochemical detection system and application thereof in pollutant detection
Through a four-electrode electrochemical detection system, combined with a multi-dimensional catalytic mode, and the use of specific quantum dots and composite membrane materials, the problem of rapid detection of new pollutants with high sensitivity and selectivity has been solved, and accurate detection of microplastics, PFAS, etc. has been achieved.
Patent Information
- Application Number
- CN202511043758.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-07-28
AI Technical Summary
Existing pollutant detection technologies are costly, require complex equipment, and are difficult to achieve rapid detection with high sensitivity and selectivity, especially for emerging environmental pollutants such as microplastics and PFAS.
A four-electrode electrochemical detection system is adopted, using materials such as MoS2/ZnO core-shell quantum dots, ZnS:Cu quantum dots, graphene quantum dots and PVDF-TrFE composite membrane, combined with static adsorption catalysis, dynamic electrochemical catalysis and photoelectric synergistic catalysis modes to improve detection sensitivity and selectivity.
It has achieved rapid and accurate detection of new pollutants with a sensitivity of ppb level, and can effectively detect a variety of new pollutants. The equipment is simple, environmentally friendly and does not produce hazardous waste.
Smart Images

Figure CN120801456A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of electrochemical sensors, and particularly relates to a four-electrode electrochemical detection system for realizing high-sensitivity and high-selectivity rapid detection of microplastics, PFAS and other pollutants in environmental water samples and food substrates. BACKGROUND
[0002] With the advancement of industrialization and urbanization, more and more new chemical substances are widely used in industrial production, agriculture, medical treatment and daily life. Emerging contaminants (ECs) refer to a class of new environmental pollutants that have not been or have just been included in the traditional environmental monitoring and management system. These pollutants include pharmaceuticals and personal care products (PPCPs), perfluoro and polyfluoro alkyl substances (PFASs), hormones, antibiotics, endocrine disruptors, microplastics, nanomaterials and the like. Emerging contaminants have the characteristics of various types, diverse structures, strong biological activity, high concealment, low environmental concentration but potential harm, and have become a research hotspot in the field of global environment and health.
[0003] The content of emerging contaminants in the environment is usually low, and the form is complex, so it is difficult to detect and analyze. The commonly used detection techniques at present include pretreatment techniques such as solid-phase extraction, solid-phase microextraction, liquid-liquid extraction; chromatographic techniques such as gas chromatography-mass spectrometry, high-performance liquid chromatography-mass spectrometry, ultra-high-performance liquid chromatography; mass spectrometry techniques such as triple quadrupole mass spectrometry, quadrupole-time-of-flight mass spectrometry, and high-resolution mass spectrometry. However, these methods are very costly, mainly requiring expensive instruments and equipment, and also require complex pretreatment steps and excessive solvents. Therefore, compared with other analysis methods, electrochemistry has the technical advantages of low cost, easy to use, high sensitivity and rapidity. In addition, electrochemical sensors are smaller in size and use various nanomaterials to modify the surface of the electrode to improve sensitivity and selectivity. Electrochemical sensing technology is considered a clean technology because they do not generate hazardous waste and allow measurements to be made using small amounts of chemicals and samples. The existing four-electrode detection system has significant advantages in improving the accuracy of electrochemical testing and revealing the intrinsic behavior of the electrode / interface, but there are still many technical and theoretical problems to be solved, such as assembly process, reference electrode stability, signal interference, complex data interpretation, test equipment adaptation, miniaturization compatibility, etc. SUMMARY
[0004] The present application provides a four-electrode electrochemical detection system, which realizes rapid and accurate detection of emerging contaminants, especially in the fields of environment and food, by using the four-electrode electrochemical detection system. The four-electrode electrochemical detection system improves the detection sensitivity and resolution through multi-dimensional detection mode, and can effectively detect a variety of emerging contaminants.
[0005] The four-electrode electrochemical detection system of the application comprises an anode, a cathode, a reference electrode I and a reference electrode II.
[0006] The preparation of the anode is as follows: (1) MoS2 nanosheets 1.2-2.0 g are placed in 60-80 mL of distilled water, stirred and mixed, and then subjected to hydrothermal reaction at 175-185 ℃ for 7-9 h, and then naturally cooled, centrifuged, and the supernatant collected to obtain a MoS2 quantum dot solution; ZnO is placed in distilled water, mixed, and then subjected to hydrothermal reaction at 175-185 ℃ for 7-9 h, and then naturally cooled, centrifuged, and the precipitate collected, washed and dried to obtain ZnO quantum dots, 10-15 mL of deionized water is added to 90-110 mg of the ZnO quantum dots, and then ultrasonically mixed to obtain a ZnO quantum dot solution; the MoS2 quantum dot solution is mixed with a 1.0 mM HCl solution to obtain a mixed solution, and the ZnO quantum dot solution is added dropwise to the mixed solution under stirring, and the pH is adjusted to 8-10 during the dropwise addition, and then the reaction is carried out at 55-65 ℃ for 2 h to obtain MoS2 / ZnO core-shell quantum dots; The volume ratio of the mixed solution to the ZnO quantum dot solution is 1-3:1, and the volume ratio of the MoS2 quantum dot solution to the HCl solution is 10:1.
[0007] (2) Cu(NO3)2 is added to a Zn(NO3)2 solution, stirred and mixed, and then a thiourea solution is added dropwise to the nitrate mixed solution, and then ethylenediamine is added, sealed, and then subjected to reaction at 190-210 ℃ for 10-15 h, and then naturally cooled, centrifuged, and the precipitate collected, washed and dried, and then annealed at 450-550 ℃ under N2 atmosphere for 2 h, and then cooled to obtain ZnS:Cu quantum dots; The mass ratio of Zn(NO3)2 to Cu(NO3)2 is 20-30:1, the mass ratio of Cu(NO3)2 to thiourea is 5-8:1, and the mass-volume ratio of Cu(NO3)2 to ethylenediamine is 1:5-10 mg:μL; ZnS:Cu quantum dots are weighed and dispersed in chloroform, 3-aminopropyl triethoxysilane is added, and then refluxed at 55-65 ℃, centrifuged, and the solid washed with chloroform for 2-3 times, and then vacuum dried to obtain modified ZnS:Cu quantum dots; The mass-volume ratio of the ZnS:Cu quantum dots to 3-aminopropyl triethoxysilane is 1:1-3 mg:μL; 100-150 mg of graphene quantum dots are dispersed in N,N-dimethylformamide, 100 μL of carbodiimide and 50 μL of N-hydroxysuccinimide are added, stirred at room temperature for 2 h, and then 20 mg of PVDF-TrFE oligomer is added, and the reaction product is dialyzed in a dialysis bag with a molecular weight cut-off of 500 Da for 24 h, and then freeze-dried to obtain functionalized graphene quantum dots. 1.0-2.5 g of PVDF-TrFE oligomer and 100-150 mg of polyvinyl pyrrolidone were added to a 0.1 M N,N-dimethylformamide aqueous solution and stirred at 60°C until completely dissolved to prepare a PVDF-TrFE solution; modified ZnS:Cu quantum dots and functionalized graphene quantum dots were separately dispersed in DMF and sonicated for 30 minutes; the sonicated modified ZnS:Cu quantum dot solution was dropwise added to the PVDF-TrFE solution and stirred, and then the functionalized graphene quantum dot solution was added and sonicated. After stirring at room temperature overnight, the solution was filtered through a 0.45 μm polytetrafluoroethylene filter to prepare a PVDF-TrFE / ZnS:Cu / GQDs composite solution; The mass ratio of the modified ZnS:Cu quantum dots to the PVDF-TrFE oligomer is 1:20-50, and the mass ratio of the functionalized graphene quantum dots to the PVDF-TrFE oligomer is 1:30-50.
[0008] (3) The ITO substrate was cleaned with distilled water and ethanol in turn, and a MoS2 / ZnO core-shell quantum dot layer was prepared on the substrate by thermal evaporation. After drying, a PVDF-TrFE / ZnS:Cu / GQDs composite liquid was coated on the MoS2 / ZnO core-shell quantum dot layer, dried, annealed at 140°C for 2 hours, and cooled to obtain a PVDF-TrFE / ZnS:Cu / GQDs composite film layer, and finally the anode was prepared.
[0009] The cathode is prepared as follows: A. Fe3O4 nanoparticles were hydrothermally reacted with glucose at 150-200°C for 6 h, centrifuged, and the precipitate was washed 2-3 times and dried to obtain Fe3O4@C quantum dots. A polyaniline solution was mixed with Fe3O4@C quantum dots-DMF at pH 1-2, ultrasonically reacted, centrifuged, and the solid was washed and dried to obtain PANI / Fe3O4@C powder. The mass ratio of the polyaniline to the Fe3O4@C quantum dots is 1-5:1.
[0010] B. Using an electrospinning method, PANI / Fe3O4@C powder and polyacrylonitrile solution were composited to form a fiber membrane. The fiber membrane was treated at 250-300°C in an air atmosphere for 2 hours, naturally cooled to room temperature, and then kept at 750-850°C in a nitrogen atmosphere for 2 hours. The carbonized fiber membrane was cooled to obtain a carbonized fiber membrane. The mass ratio of the PANI / Fe3O4@C powder to polyacrylonitrile was 1:4-10.
[0011] C. ZnS, CaO, MnCO3 and anhydrous ethanol were mixed, ground and mixed, and reacted at 750-850℃ for 6h in nitrogen atmosphere to obtain CaZnOS:Mn 2+Nanoparticles; CaZnOS:Mn 2+ The nanoparticles are added into anhydrous ethanol to prepare a suspension by ultrasonic dispersion; the carbon fiber membrane is soaked in the suspension and dried at 200 DEG C to prepare a cathode; The mass ratio of ZnS to CaO is 1-2:1, and the mass ratio of ZnS to MnCO3 is 5-10:1. The reference electrode I is prepared by mixing zirconium oxide, sodium silicate, sodium phosphate and anhydrous ethanol, grinding and mixing uniformly, then adding 4-6% polyvinyl alcohol solution and grinding, and ultrasonic dispersion; the dispersion is spin-coated on the surface of a ZrO2 ceramic electrode, dried, then heat-treated at 280-320 DEG C for 2h, heat-treated at 1000 DEG C for 4h, naturally cooled to room temperature, soaked in 0.1M HCl solution for 30min, then washed to neutral, dried; Pt paste is coated on the surface of the dried electrode and a platinum wire is fixed, and sintered at 750-850 DEG C for 30min to prepare the reference electrode I. The mass ratio of zirconium oxide to sodium silicate is 1:1-2, and the mass ratio of sodium silicate to sodium phosphate is 1-2:1; the Pt paste is prepared by adding 5-20mg platinum powder into 0.5-2mL anhydrous ethanol, ultrasonic treatment for 10-30min, and dropwise adding 200-300ul of 5% Nafion solution, and stirring and mixing uniformly.
[0012] The reference electrode II is a silver / silver chloride electrode.
[0013] Another object of the application is to apply the above four-electrode electrochemical detection system to pollutant detection.
[0014] The four-electrode electrochemical detection system is used in the following manner: 1. Static adsorption catalysis Without applying voltage, the working electrode reacts with new pollutants using the catalytic activity of quantum dots to generate products with electrochemical signals. By measuring the concentration change of these products, the change of pollutants in the environment can be monitored in real time.
[0015] The specific adsorption of pollutants by the defect sites on the surface of quantum dots is monitored by surface plasmon resonance (SPR) to detect the change in the thickness of the adsorption layer, and the sensitivity can reach 0.1nm; the adsorption of pollutants by the defect sites on the surface of quantum dots is monitored by SPR to detect the change in the thickness of the adsorption layer, and the sensitivity can reach 0.1nm / ug.L -1 .
[0016] 2. Dynamic electrochemical catalysis Under the condition of applying low voltage and piezoelectric stimulation, the working electrode interacts with pollutants through electrochemical catalytic reaction, and generates electron flow, thereby obtaining current signal. Under this mode, the intensity of electrochemical signal is positively correlated with the concentration of pollutants, and has high sensitivity and selectivity. A scanning voltage of -0.5-1.2V is applied, a built-in electric field is formed at the quantum dot heterojunction interface, electron transfer is accelerated, and the redox peak current is detected by differential pulse voltammetry (DPV).
[0017] 3. Photoelectric synergistic catalysis Under the combined condition of applying voltage and pressure, the photoelectric catalysis of quantum dot materials is significantly enhanced. By controlling the changes of voltage, current and pressure, high-resolution electrochemical reaction data can be obtained in the shortest time, and the detection ability of the sensor for new pollutants is further improved. The generation of photoelectric reaction can provide additional detection information to help accurately measure the concentration of pollutants. Under the combination of 1.2-3.0MPa pressure, the quantum dots generate photo-generated electron-hole pairs, and the photoelectric current density (nA / cm 2 is analyzed in combination with electrochemical impedance spectroscopy (EIS).
[0018] Advantages and technical effects of the present application: The anode of the four-electrode electrochemical sensing system of the present application adopts MoS2 / ZnO core-shell quantum dots, ZnS:Cu quantum dots, graphene quantum dots and PVDF-TrFE composite film and the like materials, which combines the excellent electrochemical catalytic activity of MoS2 / ZnO core-shell quantum dots, the large specific surface area of quantum dots to expose more active sites, enhances the electron transfer efficiency and adsorption capacity. The ZnS:Cu quantum dots have unique photoelectric response characteristics, and the graphene quantum dots have excellent conductivity. The two form a film layer with PVDF-TrFE, which not only fixes the quantum dots by the mechanical stability of PVDF-TrFE, but also strengthens the electron transfer through the conductive network of graphene quantum dots, so that the oxidation reaction of pollutants is more likely to occur, the detection signal is significantly amplified, the catalytic efficiency and the adsorption performance of pollutants are improved, and the detection response is further strengthened.
[0019] The "adsorption-catalysis" dual-function design of the cathode can enhance the targeted adsorption of pollutants containing polar groups by the magnetism of Fe3O4, and improve the conductivity by the carbon shell; polyaniline (PANI) as a conductive polymer can construct an efficient electron transport channel to accelerate the reduction reaction of pollutants. The carbonized fiber membrane has a high specific surface area, CaZnOS:Mn 2+ Nanoparticles as luminescent materials can generate energy transfer under photoelectric synergistic mode, which can increase the adsorption capacity of pollutants and further activate the catalytic reaction, forming an "oxidation-reduction" closed loop with the anode to strengthen the symmetry and stability of the detection response.
[0020] Reference electrode I takes zirconium oxide, sodium silicate and sodium phosphate as base materials, and the conductivity is improved after modification of Pt, so that the reference potential can be stably output; the double reference can correct the potential drift in real time, so that the working potential of the anode and the cathode is always in the best interval, and the anti-interference ability is fundamentally improved.
[0021] The "multi-dimensional" effect of the three catalytic modes, static adsorption catalysis through high adsorption of the electrode material, trace pollutants fully adhere to the electrode surface without external force interference, solving the problem of "difficult to contact active sites" of low concentration pollutants; dynamic electrochemical catalysis increases the collision frequency of pollutants and electrodes, reduces the mass transfer resistance, so that more pollutants participate in electrochemical reaction, and improves the detection efficiency; pressurized photoelectric synergistic catalysis promotes the diffusion of pollutants to the electrode surface through pressurized environment, and excites ZnS:Cu, CaZnOS:Mn 2+ The equivalent quantum dots generate photo-induced electron-hole pairs, and form "light-electricity-pressure" synergy with electrochemical catalysis to accelerate the oxidation and reduction of pollutants, and the detection line can reach ppb level. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 It is a PET microplastic (MP) concentration and peak current standard curve graph of Example 1; Figure 2 It is a Cr 6+ concentration and peak current standard curve graph of Example 1; Figure 3 It is a Ciprofloxacin (CIP) concentration and peak current standard curve graph of Example 1; Figure 4 It is a PET phthalate (PAEs) concentration and peak current standard curve graph of Example 2; Figure 5 It is a PET perfluorooctane sulfonic acid (PFOS) concentration and peak current standard curve graph of Example 2; Figure 6 It is a PET naphthalene (NAP) concentration and peak current standard curve graph of Example 2. DETAILED DESCRIPTION
[0023] The application will be further described in detail by examples, but the protection scope of the application is not limited to the content described, and the methods in the examples are all conventional methods unless otherwise specified, and the reagents used are all conventional commercially available reagents or reagents prepared according to conventional methods unless otherwise specified.
[0024] 1. Preparation of anode (1) MoS2 nanosheets 1.6 g were placed in 70 mL of distilled water, stirred and mixed, and then hydrothermally reacted at 180°C for 8 h. After natural cooling, centrifugation was performed at 8000 rpm for 15 min, and the supernatant was collected to obtain a MoS2 quantum dot solution. 0.81 g of ZnO was placed in 70 mL of distilled water, mixed, and then hydrothermally reacted at 180°C for 8 h. After natural cooling, centrifugation was performed at 8000 rpm for 15 min, and the precipitate was collected, washed, and dried to obtain ZnO quantum dots. 10 mL of deionized water was added to 100 mg of the ZnO quantum dots, which were then ultrasonically mixed to obtain a ZnO quantum dot solution. 20 mL of the MoS2 quantum dot solution was mixed with 2 mL of a 1.0 mM HCl solution to obtain a mixed solution. The ZnO quantum dot solution 10 mL was added dropwise to the mixed solution under stirring, and the pH was adjusted to 9 during the dropwise addition. After the dropwise addition was completed, the reaction was performed at 60°C for 2 h to obtain MoS2 / ZnO core-shell quantum dots.
[0025] (2) 2.88 g of Zn(NO3)2·6H2O was weighed into a beaker, 30 mL of deionized water was added, and magnetic stirring was performed until complete dissolution. 115 mg of Cu(NO3)2·3H2O was weighed into the beaker, and stirring was continued until uniform. The mixture was transferred to a 50 mL volumetric flask, and the volume was adjusted and shaken (the mass ratio of Zn(NO3)2 to Cu(NO3)2 was 25:1) to obtain a mixed solution. 19.1 mg of thiourea (the mass ratio of Cu(NO3)2·3H2O to thiourea was 6:1) was weighed into a beaker, 20 mL of deionized water was added, and stirring was performed at room temperature until dissolution. The volume was adjusted to 30 mL, and shaking was performed. The thiourea solution was slowly added dropwise to the above-mentioned mixed solution, and 690 μL of ethylenediamine chelating agent (the mass-volume ratio of Cu(NO3)2·3H2O to ethylenediamine was 1:6 mg: μL) was added to form a white ZnS precursor precipitate. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined reaction kettle, sealed, and reacted at 200°C for 12 h. After natural cooling, centrifugation was performed at 8000 rpm for 10 min, and the precipitate was collected, washed with deionized water and anhydrous ethanol three times each, and dried at 60°C for 12 h. Annealing was performed at 500°C for 2 h under a N2 atmosphere, and after cooling, ZnS:Cu quantum dots were obtained. 120 mg of the ZnS:Cu quantum dots was weighed, dispersed in 20 mL of chloroform, and 120 μL of 3-aminopropyltriethoxysilane was added. Reflux reaction was performed at 60°C for 2 h, centrifugation was performed at 10000 rpm for 10 min, the solid was washed with chloroform three times, and vacuum drying was performed at 60°C to obtain modified ZnS:Cu quantum dots. The 100 mg graphene quantum dots were dispersed in 10 mL of N,N-dimethylformamide, 100 μL of carbodiimide and 50 μL of N-hydroxysuccinimide were added, and stirring was performed at room temperature for 2 h, then 20 mg of PVDF-TrFE oligomer was added, and stirring was continued, and the reaction product was dialyzed in a dialysis bag with a molecular weight cut-off of 500 Da for 24 h, and freeze-drying was performed to obtain functionalized graphene quantum dots; The 1.8 g of PVDF-TrFE oligomer and 120 mg of polyvinylpyrrolidone were added to 50 mL of 0.1 M aqueous N,N-dimethylformamide, and stirring was performed at 60°C until complete dissolution to obtain a PVDF-TrFE solution; the modified ZnS:Cu quantum dots and the functionalized graphene quantum dots were separately dispersed in DMF and ultrasonicated for 30 min; the modified ZnS:Cu quantum dot solution after ultrasonication was added dropwise to the PVDF-TrFE solution (the mass ratio of the modified ZnS:Cu quantum dots to the PVDF-TrFE oligomer was 1:30), stirring was performed, then the functionalized graphene quantum dot solution (the mass ratio of the functionalized graphene quantum dots to the PVDF-TrFE oligomer was 1:40) was added, ultrasonication was performed for 1 h, stirring was performed at room temperature overnight, and then filtration was performed using a 0.45 μm polytetrafluoroethylene filter membrane to obtain a PVDF-TrFE / ZnS:Cu / GQDs composite solution.
[0026] (3) The ITO substrate was sequentially cleaned with distilled water and ethanol, a MoS2 / ZnO core-shell quantum dot layer was prepared on the substrate by a thermal evaporation method, after drying, the PVDF-TrFE / ZnS:Cu / GQDs composite solution was coated on the MoS2 / ZnO core-shell quantum dot layer, drying was performed, annealing was performed at 140°C for 2 h, cooling was performed, a PVDF-TrFE / ZnS:Cu / GQDs composite film layer was prepared, and finally an anode was prepared.
[0027] 2. Preparation of a cathode A. Fe3O4 nanoparticles 500 mg and glucose 1.0 g were subjected to hydrothermal reaction at 180°C for 6 h, centrifugation was performed at 8000 rpm for 10 min, the precipitate was washed with deionized water for 3 times, and drying was performed at 60°C to obtain Fe3O4@C quantum dots; 260 mg of a polyaniline solution was mixed with 130 mg of Fe3O4@C quantum dots-DMF under the condition of pH 1 (the mass ratio of the polyaniline to the Fe3O4@C quantum dots was 2:1), ultrasonication was performed after reaction, centrifugation was performed, the solid was washed with deionized water, and drying was performed at 60°C to obtain PANI / Fe3O4@C powder.
[0028] B, 100 mg of PANI / Fe3O4@C powder was compounded with 8 g of polyacrylonitrile solution by electrospinning method to prepare a fiber membrane (the mass ratio of PANI / Fe3O4@C powder to polyacrylonitrile was 1:8), the fiber membrane was treated at 280°C for 2h in air atmosphere, naturally cooled to room temperature, and then heat treated at 800°C for 2h in nitrogen atmosphere, and cooled to obtain a carbonized fiber membrane.
[0029] C, 97 mg of ZnS, 56 mg of CaO, 229 mg of MnCO3, and 15 mL of anhydrous ethanol were mixed, ground and uniformly mixed, and then reacted at 800°C for 6h in a nitrogen atmosphere to obtain CaZnOS:Mn 2+ nanoparticles; the CaZnOS:Mn 2+ nanoparticles 50 mg were added into 20 mL of anhydrous ethanol to prepare a suspension by ultrasonic dispersion; the carbonized fiber membrane was soaked in the suspension for 30 min, repeated for 3 times, and dried at 200°C for 4h to obtain a cathode.
[0030] 3, Reference electrode I was prepared by mixing 61 mg of zirconia, 122 mg of sodium silicate, 81 mg of sodium phosphate, and 5 mL of anhydrous ethanol, grinding and uniformly mixing, then adding 5% polyvinyl alcohol solution and grinding, and ultrasonic dispersion; the dispersion was spin-coated on the surface of a ZrO2 ceramic electrode, dried, and then heat treated at 300°C for 2h, heat treated at 1000°C for 4h, naturally cooled to room temperature, soaked in 0.1M HCl solution for 30 min, washed with deionized water until neutral, and dried at 60°C; Pt paste was coated on the surface of the dried electrode and a platinum wire was fixed, and the Pt paste was prepared by adding 10 mg of platinum powder into 1 mL of anhydrous ethanol, ultrasonic treatment for 20 min, adding 250 μL of 5% Nafion solution dropwise, and stirring and mixing uniformly, and then sintering at 800°C for 30 min to obtain the reference electrode I.
[0031] 4, The four-electrode electrochemical sensing system was used to simultaneously detect PET microplastics (MPs), Cr 6+ and ciprofloxacin (CIP) a, Test instruments and conditions: The four-electrode electrochemical sensor includes an electrochemical workstation, an electrolytic cell, the anode, the cathode, and the reference electrode I prepared in steps 1, 2, and 3; a silver / silver chloride reference electrode II.
[0032] b, Preparation of standard curve The electrolyte in the electrolytic cell was 0.1M PBS buffer containing 35% [EMIM][BF4], and the pH was 7.0; the electrolyte contained 0~3 μmol / L of PET microplastics (MPs), 0~3 μmol / L of Cr 6+ and 0~3 μmol / L of ciprofloxacin (CIP). ① Select differential pulse voltammetry on the electrochemical workstation, set the enrichment potential to 0.1V, and the enrichment time to 60 seconds; place the magnetic stirring bar in the electrolytic cell, set the stirring speed of the electric stirrer to 300rpm, and use the electrochemical workstation to record the change in current-voltage to obtain the current-voltage curve; ② After the enrichment time is over, immediately stop stirring the solution in the electrolytic cell, let it stand for 5s, load a scanning voltage in the range of -0.5V to 1.2V on the working electrode, and use the electrochemical workstation to record the change in current-voltage to obtain the current-voltage curve. ③ Let it stand for another 5s, load an external voltage of 1.2-3.0MPa on the working electrode, and use the electrochemical workstation to record the change in current-voltage to obtain the current-voltage curve. ④ Record the characteristic peak currents of the three pollutants, and measure each concentration gradient in parallel 3 times; PET microplastics (MPs), Cr 6+ , ciprofloxacin (CIP) concentration as the horizontal axis, and the peak current value as the vertical axis, and the PET microplastics (MPs), Cr 6+ , ciprofloxacin (CIP) corresponding standard curve, linear regression, to obtain PET microplastics (MPs), Cr 6+ , the linear relationship between the concentration of ciprofloxacin (CIP) and the peak current; this linear relationship (standard curve) is used to quantitatively detect the PET microplastics (MPs), Cr 6+ , ciprofloxacin (CIP) concentration; PET microplastics (MPs), Cr 6+ The linear relationships between ciprofloxacin (CIP) concentration and peak current are: PET microplastics (MPs): I p =3.0251×C MPs + 0.0023 (R 2 =0.9987), MPs concentration was 0.08~3.0 μmol / L; Cr 6 ⁺: I p =4.1063×C Cr6+ +0.0090(R 2 =0.9991), Cr 6+ Concentration ranges from 0.08 to 3.0 μmol / L; Ciprofloxacin (CIP) I p = 2.5960×C CIP +0.0086 (R 2 =0.9979), CIP concentration was 0.08~3.0 μmol / L; c. Calculation of detection limit The detection limit was performed at an enrichment time of 60 seconds, and the detection limit was calculated by the formula CL = 3Sb / m, where CL, Sb and m are the detection limit (pmol / L), the blank standard deviation (pA) and the standard curve slope (pA / (pmol / L)), respectively. The standard curve slope was obtained by step b, and was PET microplastics (MPs): 3.0251; Cr 6+ : 4.1063; Ciprofloxacin (CIP) 2.5960: The blank standard deviation was obtained by taking the standard deviation of the peak current value of 10 blank water samples, and was PET microplastics (MPs): 0.0214; Cr 6+ : 0.0297; Ciprofloxacin (CIP): 0.0273; Finally, the standard curve slope and the blank standard deviation were brought into the formula CL = 3Sb / m to obtain the electrode detection limit, which was PET microplastics (MPs): 0.0291 pmol / L; Cr 6+ : 0.0214 pmol / L; Ciprofloxacin (CIP): 0.0267 pmol / L.
[0033] d. Detection of the sample to be tested The electrolyte containing 2 pmol / L PET microplastics (MPs), 2 pmol / L Cr 6+ and 2 pmol / L Ciprofloxacin (CIP) was detected, and the experimental method was step b, and the peak currents of PET microplastics (MPs), Cr 6+ and Ciprofloxacin (CIP) were 5.8104 pA, 7.7700 pA and 4.7074 pA, respectively. Then the peak current values were substituted into the linear equation of step b, and the contents of PET microplastics (MPs), Cr 6+ and Ciprofloxacin (CIP) were calculated to be 1.92 pmol / L and 1.89 pmol / L, 1.81 pmol / L, respectively.
[0034] e. Electrode stability test The same electrode was placed at room temperature for 30 days, and the test current value at 30 days was 94.1%, 96.8%, 95.3% of the initial value, corresponding to PET microplastics (MPs), Cr 6+ and Ciprofloxacin (CIP), indicating that the sensor has good stability.
[0035] Example 2: Using the four-electrode electrochemical detection system of Example 1 to simultaneously detect phthalate esters (PAEs), perfluorooctane sulfonic acid (PFOS) and naphthalene (NAP) a. Test instruments and conditions The four-electrode electrochemical sensor system was prepared and connected as in Example 1; b. Preparation method of standard curve The process is the same as that in Example 1 The electrolyte containing phthalate esters, PFOS and naphthalene with the concentration ranging from 0 to 3.0 μmol / L was configured. The linear relationship between the concentration of phthalate esters (PAEs), PFOS and naphthalene (NAP) and the peak current was obtained. Phthalate esters (PAEs): I p = 3.2165xC PAEs + 1.1461 (R 2 = 0.9987) when the concentration of PAEs was 0.08-3.0 μmol / L. PFOS: I p = 2.8541xC PFOS + 0.8767 (R 2 = 0.9997) when the concentration of PFOS was 0.08-3.0 μmol / L. Naphthalene (NAP) I p = 3.7856xC NAP + 1.9767 (R 2 = 0.9979) when the concentration of NAP was 0.08-3.0 μmol / L. c. Calculation of detection limit The detection limit was obtained at the enrichment time of 60 seconds. The detection limit was calculated by the formula CL= 3Sb / m, wherein CL, Sb and m were the detection limit (μmol / L), the standard deviation of blank (μA) and the slope of standard curve (μA / (μmol / L), respectively. The slope of standard curve was obtained by step b, and was 3.2165 for phthalate esters (PAEs), 2.8541 for PFOS and 3.7856 for naphthalene (NAP), respectively. The standard deviation of blank was obtained by scanning the peak current value of the blank water sample for 10 times, and was 0.0314 for phthalate esters (PAEs), 0.0307 for PFOS and 0.0373 for naphthalene (NAP), respectively. Finally, the slope of standard curve and the standard deviation of blank were brought into the formula CL= 3Sb / m to obtain the detection limit of the electrode, which was 0.0391 μmol / L for phthalate esters (PAEs), 0.0314 μmol / L for PFOS and 0.0467 μmol / L for naphthalene (NAP).
[0036] d. Detection of sample to be detected The complex electrolyte containing phthalate esters with a concentration of 2 μmol / L, 2 μmol / L perfluorooctane sulfonic acid and 2 μmol / L naphthalene (NAP) was detected, and the experimental method was step b. The peak currents of phthalate esters (PAEs), perfluorooctane sulfonic acid (PFOS) and naphthalene (NAP) were 7.1609 μA, 5.8123 μA and 9.3208 μA, respectively. Then the peak current values were substituted into the linear equation of step b, and the contents of phthalate esters, perfluorooctane sulfonic acid and naphthalene were calculated as 1.87 μmol / L, 1.91 μmol / L and 1.94 μmol / L, respectively.
[0037] e. Electrode stability test The same electrode was placed at room temperature for 30 days, and the test current value at 30 days was 96.3%, 95.8% and 94.3% of the initial value corresponding to phthalate esters (PAEs), perfluorooctane sulfonic acid (PFOS) and naphthalene (NAP), respectively, indicating that the sensor has good stability.
[0038] Example 3: Four-electrode electrochemical detection system and simultaneous detection of PET microplastics (MPs) and Cr 6+ Preparation of anode with ciprofloxacin (CIP) 1 (1) MoS2 nanosheets 1.2 g were placed in 60 mL of distilled water, stirred and mixed, then hydrothermal reaction was carried out at 185 ℃ for 7 h, and then naturally cooled, centrifuged at 8000 rpm for 15 min, and the supernatant was collected to obtain MoS2 quantum dot solution; 0.81 g of ZnO was placed in 70 mL of distilled water, mixed, then hydrothermal reaction was carried out at 180 ℃ for 8 h, and then naturally cooled, centrifuged at 8000 rpm for 15 min, and the precipitate was collected, washed and dried to obtain ZnO quantum dots. 12 mL of deionized water was added to 95 mg of ZnO quantum dots, and the mixture was ultrasonically mixed to obtain a ZnO quantum dot solution. MoS2 quantum dot solution 20 mL and 1.0 mM HCl solution 2 mL were mixed to obtain a mixed solution, and ZnO quantum dot solution 10 mL was added dropwise to the mixed solution under stirring, and the pH was adjusted to 9 during the dropwise addition. After the dropwise addition was completed, the reaction was carried out at 55 ℃ for 2 h to obtain MoS2 / ZnO core-shell quantum dots.
[0039] (2) 2.98 g Zn(N03)2-6H20 was weighed into a beaker, 30 ml deionized water was added, and magnetic stirring was performed until complete dissolution. 149 mg Cu(N03)2-3H20 was weighed into the beaker, and stirring was continued until uniform. The mixture was transferred to a 50 mL volumetric flask, and the volume was made up with deionized water (the mass ratio of Zn(N03)2to Cu(N03)2was 20:1). 24.8 mg of thiourea (the mass ratio of Cu(N03)2-3H20 to thiourea was 6:1) was weighed into a beaker, 20 mL of deionized water was added, and stirring was performed at room temperature until dissolution. The volume was made up to 30 mL with deionized water, and the mixture was shaken until uniform. The thiourea solution was slowly added dropwise to the above mixture, 1.19 mL of ethylenediamine chelating agent (the mass-volume ratio of Cu(N03)2-3H20 to ethylenediamine was 1:8), and a white ZnS precursor precipitate was formed. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined reaction kettle, sealed, and reacted at 200°C for 12 h. After natural cooling, centrifugation was performed at 8000 rpm for 10 min, the precipitate was collected, washed with deionized water and anhydrous ethanol three times, dried at 60°C for 12 h, and annealed at 500°C for 2 h under a N2atmosphere. After cooling, ZnS:Cu quantum dots were prepared. 120 mg of ZnS:Cu quantum dots were dispersed in 20 mL of chloroform, 120 μL of 3-aminopropyltriethoxysilane was added, and refluxing was performed at 60°C for 2 h. Centrifugation was performed at 10000 rpm for 10 min, the solid was washed with chloroform three times, and vacuum drying was performed at 60°C to obtain modified ZnS:Cu quantum dots. 100 mg of graphene quantum dots were dispersed in 10 mL of N,N-dimethylformamide, 100 μL of carbodiimide and 50 μL of N-hydroxysuccinimide were added, stirring was performed at room temperature for 2 h, and then 20 mg of PVDF-TrFE oligomer was added. The reaction product was dialyzed in a dialysis bag with a molecular weight cutoff of 500 Da for 24 h, and freeze-drying was performed to obtain functionalized graphene quantum dots. 2.1 g of PVDF-TrFE oligomer and 140 mg of polyvinylpyrrolidone were added to 50 mL of 0.1 M N,N-dimethylformamide aqueous solution, and stirring was performed at 60°C until complete dissolution to obtain a PVDF-TrFE solution. The modified ZnS:Cu quantum dots and the functionalized graphene quantum dots were each dispersed in DMF and ultrasonicated for 30 min. The ultrasonicated modified ZnS:Cu quantum dot solution was added dropwise to the PVDF-TrFE solution (the mass ratio of the modified ZnS:Cu quantum dots to the PVDF-TrFE oligomer was 1:35), stirring was performed, and then the functionalized graphene quantum dot solution was added (the mass ratio of the functionalized graphene quantum dots to the PVDF-TrFE oligomer was 1:42). Ultrasonication was performed for 1 h, stirring was performed at room temperature overnight, and then filtration was performed using a 0.45 μm polytetrafluoroethylene filter membrane to obtain a PVDF-TrFE / ZnS:Cu / GQDs composite solution.
[0040] (3) The ITO substrate was cleaned with distilled water and ethanol in turn, and a MoS2 / ZnO core-shell quantum dot layer was prepared on the substrate by thermal evaporation. After drying, a PVDF-TrFE / ZnS:Cu / GQDs composite liquid was coated on the MoS2 / ZnO core-shell quantum dot layer, dried, annealed at 140°C for 2 hours, and cooled to obtain a PVDF-TrFE / ZnS:Cu / GQDs composite film layer, and finally the anode was prepared.
[0041] 2. Preparation of cathode A. 500 mg of Fe3O4 nanoparticles and 1.0 g of glucose were hydrothermally reacted at 180°C for 6 h, centrifuged at 8000 rpm for 10 min, and the precipitate was washed three times with deionized water and dried at 60°C to obtain Fe3O4@C quantum dots. 520 mg of polyaniline solution was mixed with 130 mg of Fe3O4@C quantum dots-DMF at pH 1 (the mass ratio of polyaniline to Fe3O4@C quantum dots was 4:1). After ultrasonic reaction, the mixture was centrifuged, the solid was washed with deionized water, and dried at 60°C to obtain PANI / Fe3O4@C powder. B. Fiber membranes were prepared by electrospinning 100 mg of PANI / Fe3O4@C powder and 6 mL of polyacrylonitrile solution (the mass ratio of PANI / Fe3O4@C powder to polyacrylonitrile was 1:6). The fiber membranes were treated at 280°C in air for 2 h, cooled naturally to room temperature, and then kept at 800°C in nitrogen for 2 h. The carbonized fiber membranes were then cooled. C. Mix 97 mg ZnS, 56 mg CaO, 229 mg MnCO3, and 15 mL anhydrous ethanol, grind and mix well, and react at 800 ° C for 6 h in a nitrogen atmosphere to obtain CaZnOS:Mn 2+ Nanoparticles; CaZnOS:Mn 2+ Nanoparticles 50mg Add 20 mL of anhydrous ethanol and disperse by ultrasonication to prepare a suspension; soak the carbon fiber membrane in the suspension for 30 minutes, repeat 3 times, and dry at 200°C for 4 hours to prepare a cathode.
[0042] 3、Reference electrode I is to mix 61 mg of zirconium oxide, 122 mg of sodium silicate, 81 mg of sodium phosphate, 5 mL of anhydrous ethanol, grind and mix uniformly, then add 5% polyvinyl alcohol solution and grind, ultrasonic dispersion; the dispersion is spin-coated on the surface of the ZrO2 ceramic electrode, dried, then heat treated at 300°C for 2h, heat treated at 1000°C for 4h, naturally cooled to room temperature, soaked in 0.1M HCl solution for 30min, then washed with deionized water until neutral, dried at 60°C; Pt paste is coated on the surface of the dried electrode and a platinum wire is fixed, sintered at 800°C for 30min, wherein the Pt paste is prepared by adding 10mg of platinum powder to 1mL of anhydrous ethanol, ultrasonic treatment for 20min, adding 250μL of 5% Nafion solution dropwise, and stirring uniformly.
[0043] 4、The four-electrode electrochemical sensing system simultaneously detects PET microplastics (MPs), Cr 6+ and ciprofloxacin (CIP) a、Test instrument and conditions: The four-electrode electrochemical sensor includes an electrochemical workstation, an electrolytic cell, the anode, the cathode, and the reference electrode I prepared in steps 1, 2, and 3; a silver / silver chloride reference electrode II.
[0044] b、The standard curve preparation method is the same as in Example 1; c、The calculation of the detection limit is the same as in Example 1; d、Detection of the sample to be tested The 0.1M PBS buffer containing 0.6μmol / L PET microplastics (MPs), 0.6μmol / L and Cr 6+ and 0.6μmol / L ciprofloxacin (CIP) is detected in a complex electrolyte of 35%wt[EMIM][BF4], the experimental method is the same as step b, and the content of PET microplastics (MPs), Cr 6+ and ciprofloxacin (CIP) is calculated to be 0.563μmol / L and 0.579μmol / L, 0.591μmol / L, respectively.
[0045] e、Electrode stability test The same electrode is placed at room temperature for 30 days, and the test current value at 30 days is 94.1%, 93.8%, and 94.6% of the initial value corresponding to PET microplastics (MPs), Cr 6+ and ciprofloxacin (CIP), indicating that the sensor has good stability.
Claims
1. A four-electrode electrochemical detection system, characterized in that: Including anode, cathode, reference electrode I and reference electrode II; The anode is prepared as follows: (1) Place 1.2-2.0 g of MoS2 nanosheets in 60-80 mL of distilled water, stir and mix, and then hydrothermally react at 175-185 ° C for 7-9 h, cool naturally, centrifuge, collect the supernatant to obtain MoS2 quantum dot solution; place ZnO in distilled water, mix, and hydrothermally react at 175-185 ° C for 7-9 h, cool naturally, centrifuge, collect the precipitate, wash and dry to obtain ZnO quantum dots, add 10-15 mL of deionized water to 90-110 mg of ZnO quantum dots, and ultrasonically mix to obtain ZnO quantum dot solution; mix the MoS2 quantum dot solution with 1.0 mM HCl solution to obtain a mixed solution, and add the ZnO quantum dot solution dropwise to the mixed solution under stirring, adjust the pH to 8-10 during the addition process, and react at 55-65 ° C for 2 h after the addition to obtain MoS2 / ZnO core-shell quantum dots; (2) Add Cu(NO3)2 to Zn(NO3)2 solution, stir and mix, then add thiourea solution dropwise to the nitrate mixed solution, then add ethylenediamine, seal and react at 190-210℃ for 10-15h, cool naturally, centrifuge, collect precipitate, wash and dry, anneal in N2 atmosphere at 450-550℃ for 2h, and cool to obtain ZnS:Cu quantum dots; Weigh ZnS:Cu quantum dots and disperse them in chloroform. Add 3-aminopropyltriethoxysilane and reflux at 55-65°C. Centrifuge. Wash the solid with chloroform 2-3 times and vacuum dry to obtain modified ZnS:Cu quantum dots. 100-150 mg of graphene quantum dots were dispersed in N,N-dimethylformamide, 100 μL of carbodiimide and 50 μL of N-hydroxysuccinimide were added, and the mixture was stirred at room temperature for 2 h. Then, 20 mg of PVDF-TrFE oligomer was added and stirring was continued. The reaction product was dialyzed with a dialysis bag with a molecular weight cutoff of 500 Da for 24 h and then freeze-dried to obtain functionalized graphene quantum dots. 1.0-2.5 g of PVDF-TrFE oligomer and 100-150 mg of polyvinyl pyrrolidone were added to a 0.1 M N,N-dimethylformamide aqueous solution and stirred at 60°C until completely dissolved to prepare a PVDF-TrFE solution; modified ZnS:Cu quantum dots and functionalized graphene quantum dots were separately dispersed in DMF and sonicated; the sonicated modified ZnS:Cu quantum dot solution was dropwise added to the PVDF-TrFE solution and stirred, and then the functionalized graphene quantum dot solution was added and sonicated. After stirring at room temperature overnight, the mixture was filtered through a 0.45 μm polytetrafluoroethylene filter membrane to prepare a PVDF-TrFE / ZnS:Cu / GQDs composite solution; (3) The ITO substrate was cleaned with distilled water and ethanol in sequence, and a MoS2 / ZnO core-shell quantum dot layer was prepared on the substrate by thermal evaporation. After drying, a PVDF-TrFE / ZnS:Cu / GQDs composite liquid was coated on the MoS2 / ZnO core-shell quantum dot layer, dried, annealed at 140°C for 2 hours, and cooled to obtain a PVDF-TrFE / ZnS:Cu / GQDs composite film layer, and finally an anode was prepared; The cathode is prepared as follows: A. Fe3O4 nanoparticles were hydrothermally reacted with glucose at 150-200°C for 6 h, centrifuged, and the precipitate was washed 2-3 times and dried to obtain Fe3O4@C quantum dots. A polyaniline solution was mixed with Fe3O4@C quantum dots-DMF at pH 1-2, ultrasonically reacted, centrifuged, and the solid was washed and dried to obtain PANI / Fe3O4@C powder. B. Using an electrospinning method, PANI / Fe3O4@C powder and polyacrylonitrile solution were composited to form a fiber membrane. The fiber membrane was treated at 250-300°C in an air atmosphere for 2 hours, naturally cooled to room temperature, and then kept at 750-850°C in a nitrogen atmosphere for 2 hours. The carbonized fiber membrane was then cooled. C. ZnS, CaO, MnCO3 and anhydrous ethanol were mixed, ground and mixed, and reacted at 750-850℃ for 6h in nitrogen atmosphere to obtain CaZnOS:Mn 2+ Nanoparticles; CaZnOS:Mn 2+ The nanoparticles are added to anhydrous ethanol and ultrasonically dispersed to prepare a suspension; the carbon fiber membrane is immersed in the suspension and dried to prepare a cathode; Reference electrode I is prepared by mixing zirconium oxide, sodium silicate, sodium phosphate, and anhydrous ethanol, grinding and mixing, then adding 4-6% polyvinyl alcohol solution for grinding and ultrasonic dispersion; the dispersion is spin-coated on the surface of the ZrO2 ceramic electrode, dried, and then kept at 280-320°C for 2 hours, kept at 1000°C for 4 hours, naturally cooled to room temperature, soaked in 0.1M HCl solution for 30 minutes, rinsed to neutrality, and dried; Pt slurry is coated on the dry electrode surface and a platinum wire is fixed, and sintered at 750-850°C for 30 minutes.
2. The four-electrode electrochemical detection system according to claim 1, characterized in that: In the step (1) of preparing the anode, the volume ratio of the mixed solution to the ZnO quantum dot solution is 1-3:1, and the volume ratio of the MoS2 quantum dot solution to the HCl solution is 10:
1.
3. The four-electrode electrochemical detection system according to claim 1, characterized in that: In step (2) of the anode preparation, the mass ratio of Zn(NO3)2 to Cu(NO3)2 is 20-30:1, the mass ratio of Cu(NO3)2 to thiourea is 5-8:1; and the mass volume ratio of Cu(NO3)2 to ethylenediamine is 1:5-10 in mg:μL.
4. The four-electrode electrochemical detection system according to claim 1, characterized in that: In step (2) of the anode preparation, the mass volume ratio of ZnS:Cu quantum dots to 3-aminopropyltriethoxysilane in mg:μL is 1:1-3; the mass ratio of modified ZnS:Cu quantum dots to PVDF-TrFE oligomer is 1:20-50, and the mass ratio of functionalized graphene quantum dots to PVDF-TrFE oligomer is 1:30-50.
5. The four-electrode electrochemical detection system according to claim 1, characterized in that: In step A of cathode preparation, the mass ratio of polyaniline to Fe3O4@C quantum dots is 1-5:1; in step B, the mass ratio of PANI / Fe3O4@C powder to polyacrylonitrile is 1:4-10.
6. The four-electrode electrochemical detection system according to claim 1, characterized in that: In cathode preparation, the mass ratio of ZnS to CaO is 1-2:1, and the mass ratio of ZnS to MnCO3 is 5-10:
1.
7. The four-electrode electrochemical detection system according to claim 1, characterized in that: The mass ratio of zirconium oxide to sodium silicate is 1:1-2, and the mass ratio of sodium silicate to sodium phosphate is 1-2:
1. The Pt slurry is prepared by adding 5-20 mg of platinum powder to 0.5-2 mL of anhydrous ethanol, ultrasonically treating for 10-30 minutes, dropwise adding 200-300 μL of 5% Nafion solution, and stirring to mix.
8. The four-electrode electrochemical detection system according to claim 1, characterized in that: The reference electrode II is a silver / silver chloride electrode.
9. Use of the four-electrode electrochemical detection system according to claim 1 in pollutant detection.
Citation Information
Patent Citations
Nano-gold / molybdenum disulfide combined electrode and preparation method thereof and electrochemical sensor and application thereof
CN108593733A
ZnS / AlP / GaP heterostructure thin-film material, and preparing method and application thereof
CN110724907A
Preparation method and application of TiN-MoS2 composite electrode material
CN117292954A
Preparation method and application of MoS2 / Fe2O3-coated Fe-MOF modified carbon electrode
CN119409314A
Electrochemical Biosensor and the Manufacturing Method Thereof
US20240230579A1
